Study of Broiler Chicken Meat Quality in Different Traditional Markets in Sukoharjo Regency - Kiky Ayumasari; Sri Sukaryani; Ludfia Windyasmara (Bantara Journal of Animal Science, 2020)
The aim of this study was to determine the quality of broiler chicken meat that sold at different traditional markets in Sukoharjo Regency. This study was conducted in the Laboratory Faculty of Agriculture, Animal Husbandry, Bangun Nusantara University Sukoharjo. This study was conducted in 2 weeks. The research method uses RAL (Completely Randomized Design) directional pattern. Then data was analyzed using by Anova (Analysiss of variance). The real effect of treatment was continued with the DMRT test (Duncan Multiple Range Test) to find out the differences between treatments. The observational parameters of the study include the pH levels test, water levels test, dissolved protein levels test, cooking loss levels and fat levels test. The results showed that different markets had no real effect (P>0,05) on the pH levels test, water levels test, cooking loss levels and have a real impact (P<0,05) on the dissolved protein levels test and fat levels test. Keywords : Traditional Market; Quality of Meat; Broiler Chicken.